Spirit Matters The Transcendant in Modern Japanese Literature - Gabriel, Philip (University of Hawaii Press, 2006)
Spirit Matters is a ground-breaking work, the first to explore a broad range of writings on spirituality in contemporary Japanese literature. It draws on a variety of literary works, from enormously popular fiction (Miura Ayako's Hyôten and Shirokari Pass and the novels of Murakami Haruki) to more problematic "serious" fiction (Ôe Kenzaburô's Somersault) to nonfiction meditations on martyrdom and miracles (Sono Ayako's Kiseki) and the dynamics of religious cults (Murakami's interviews with members of Aum Shinrikyô in Underground). The first half of the volume focuses on the work of two women Christian writers, Miura Ayako and Sono Ayako. Combining a decidedly evangelistic bent with the formulas of the popular novel, Miura's 1964 novel Hyôten (Freezing Point) and its sequel are entertaining perennial bestsellers but also treat spiritual issues-like original sin-that are largely unexplored in modern Japanese literature. Sono's Kiseki (Miracles) and Miura's Shiokari Pass focus on the meaning of self-sacrifice and the miraculous and survey both the paths by which people come to faith and the spiritual doubts that assail them. Perhaps most striking for Western readers, Gabriel reveals how Miura's novel shows the lingering resistance to Christianity and its oppositional nature in Japan, and how in Kiseki Sono considers the kind of spiritual struggles many Japanese Christians experience as they try to reconcile their belief in a minority faith